Angeles City Women's Center " fostering the welfare of sex workers through social reintegration - Padua, Maria Isabel; Sicam, Olivia Alma G. (Quezon City College of Architecture, University of the Philippines Diliman, 2018)
This comprehensive design situated in Angeles City, Pampanga aims to provide a variety of welfare and support services to women entertainers. The challenge was to design a center that accommodates the various needs of the estimated 15,000 or more women entertainers in the city with end goals of social reintegration, reduced stigma on sex workers, and alternative career paths. Past and present networks of support were analyzed, both government and non-government based, to ensure services address a variety of needs, ranging from physical and medical health ; psychological support and counseling; crisis and trauma support, peer groups; security, legal, financial, and career assistance; continuing education and skills training; as well as a forum for networking and career advancement. Key resource persons were interviewed on how to best emphasize their inherent and potential value to society and their community. Thus, the proposed Angeles City Women's Center provides a support network for women entertainers through the consolidation of services and facilities aimed at reintegrating them into society.
Include appendices
Thesis (Bachelor of Science in Architecture)--University of the Philippines Diliman
Keywords: Community centers; Community centers -- Philippines -- Pampanga